Characterization of Ready-to-Drink Decaffeinated Coffee Enriched with Lime and Lemon - Kuswardhani, Nita; Hana, Dania Mazidatul; Wiyono, Andi Eko (Department of Agroindustrial Technology, Faculty of Agricultural Technology UGM, 2025)
This study aims to determine the physical, chemical, and sensory characteristics of and the appropriate and optimal formulation for producing ready-to-drink (RTD) robusta decaffeinated coffee variations with the addition of lime (citrus aurantifolia) and lemon (citrus limon) juice. The ingredients used for coffee preparation include decaffeinated robusta coffee powder, lemon, lime, sugar, and water. The experimental design used in this study was a completely randomized design (CRD) with three factors and two levels: citrus type (A1: lemon; A2: lime), lemon or lime juice concentration (B1: 5%; B2: 10%), and liquid sugar volume (C1: 15 ml; C2: 25 ml). These factors were designed to create 8 treatments for physical, chemical, and sensory testing. Data analysis was performed statistically using Analysis of Variance (ANOVA) at 5% significance level and further testing with Duncan's Multiple Range Test (DMRT) when any differences were found. The results showed that the interaction of the three factors affected the physical and chemical characteristics of caffeine content, pH, and antioxidant activity. The addition of lime and lemon juice did not have a significant effect on the characteristics of vitamin C content and brightness. Treatment A1B1C2, with the composition of 5 ml lemon juice and 25 ml sugar water, provides the best formulation based on the review of physical, chemical, and sensory characteristics.